The influence of hardworking character on student academic achievement in yogyakarta - Naufal Dzaky Alfawazsyah; Tumin (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the influence of the character of hard work on the academic achievement of students in Yogyakarta. The research method used is quantitative with an associative approach. The research sample consisted of 150 active students for at least the third semester who were selected through purposive sampling techniques. The variables of hardworking character were measured using a questionnaire on a Likert scale of 1–4, while academic achievement was measured based on the most recent GPA. Data analysis was carried out by simple linear regression using SmartPLS. The results showed that the character of hard work had a positive and significant effect on academic achievement, with a path coefficient of 0.776 (p = 0.000) and an R² value of 0.602. This means that the character of hard work is able to explain 60.2% of the variation in students' academic achievement. The research instrument was declared valid (load factor > 0.7; AVE > 0.5) and reliable (Cronbach's Alpha > 0.89). These findings reinforce the theory of personality, specifically the dimension of conscientiousness, which places hard work as a predictor of academic success. In addition, these findings are in line with a humanistic view that emphasizes the importance of intrinsic motivation and perseverance to achieve academic goals. This study recommends that universities develop a program to develop hard-working character development programs through soft skills training, habituation of challenging tasks, and conducive learning environment support. This effort is expected to improve academic quality as well as the readiness of graduates to face the world of work. Further research is recommended using a more diverse sample and considering mediating variables such as learning motivation or social support to provide a more comprehensive picture.